Reformasi Ekonomi Melalui Bursa: Peran Strategis Danantara di Pasar Saham - Bok Rok Su; Wilma Silalahi (CV Rewang Rencang, 2025)
This study aims to analyze the strategic role of Danantara in supporting economic reform through its participation in the Indonesian stock market. In the digital economy era, strengthening the capital market is a crucial component to accelerating inclusive and sustainable economic growth. Danantara, as an entity that integrates technology and finance, holds significant potential in accelerating the transformation of the economic structure by enhancing the investment ecosystem. The research methodology employs a qualitative-descriptive approach through literature review, participatory observation, and in-depth interviews with capital market industry players and Danantara’s management. The results indicate that Danantara acts as a bridge between retail investors and the small-to-medium business sector by providing a platform that expands access and transparency in stock trading. Moreover, Danantara contributes to economic reform by improving financial literacy and encouraging broader public participation in the capital market. This role directly strengthens national financial stability and promotes economic equity. However, challenges remain in the form of regulation, technological infrastructure, and cross-sectoral integration, which require further development. Thus, Danantara’s involvement in the stock exchange not only impacts market dynamics but also serves as a key element in a national economic reform agenda that is more modern and adaptive to technological advancements.